2018
DOI: 10.1109/tse.2017.2757486
|View full text |Cite
|
Sign up to set email alerts
|

EARMO: An Energy-Aware Refactoring Approach for Mobile Apps

Abstract: The energy consumption of mobile apps is a trending topic and researchers are actively investigating the role of coding practices on energy consumption. Recent studies suggest that design choices can conflict with energy consumption. Therefore, it is important to take into account energy consumption when evolving the design of a mobile app. In this paper, we analyze the impact of eight type of anti-patterns on a testbed of 20 android apps extracted from F-Droid. We propose EARMO, a novel anti-pattern correctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 80 publications
0
54
0
Order By: Relevance
“…The unique investigation on the impact of three code smells on the performance of Android applications has been carried out by Hetch et al [36], who found some positive correlations between the studied smells and the decreasing performance in term of delayed frames and CPU usage. Finally, Morales et al [60] proposed EARMO, a refactoring tool that, besides code quality, takes into account the energy consumption when refactoring code smells detected in mobile apps. It is important to note that the authors mostly considered the code smells proposed by Fowler [10], while our work aims at understanding the impact of a large variety of Android-specific code smells on energy efficiency as well as the role of refactoring on the performance improvement of mobile apps.…”
Section: About Code Smells and Refactoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique investigation on the impact of three code smells on the performance of Android applications has been carried out by Hetch et al [36], who found some positive correlations between the studied smells and the decreasing performance in term of delayed frames and CPU usage. Finally, Morales et al [60] proposed EARMO, a refactoring tool that, besides code quality, takes into account the energy consumption when refactoring code smells detected in mobile apps. It is important to note that the authors mostly considered the code smells proposed by Fowler [10], while our work aims at understanding the impact of a large variety of Android-specific code smells on energy efficiency as well as the role of refactoring on the performance improvement of mobile apps.…”
Section: About Code Smells and Refactoringmentioning
confidence: 99%
“…In this paper, we provide a deeper investigation to determine (i) to what extent code smells affecting source code methods of mobile applications influence energy efficiency, and (ii) whether refactoring operations applied to remove them directly improves the energy efficiency of refactored methods. In particular, our investigation focuses on 9 method-level code smells specifically defined for mobile applications by Reimann et al [9] in the context of 60 Android apps belonging to the dataset provided by Choudhary et al [12]. To the best of our knowledge, this is up to date the largest study aimed at practically investigating the actual impact of these code smells on energy consumption and quantifying the extent to which refactoring code smells is beneficial for improving energy efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Palomba et al [44] showed that methods that represent a co-occurrence of Internal Setter, Leaking Thread, Member Ignoring Method, and Slow Loop, consume 87 times more energy than other smelly methods. To cope with bad practices in mobile apps, a few works proposed refactoring solutions [33], [40]. Notably, Morales et al [40] proposed EARMO, an energy-aware refactoring approach for mobile apps.…”
Section: Related Workmentioning
confidence: 99%
“…To cope with bad practices in mobile apps, a few works proposed refactoring solutions [33], [40]. Notably, Morales et al [40] proposed EARMO, an energy-aware refactoring approach for mobile apps. By analysing 20 open-source apps, they showed that refactoring antipatterns can decrease significantly energy consumption.…”
Section: Related Workmentioning
confidence: 99%
“…Many researchers are worried about where is the energy spent inside different applications and suggest their methods or tools for identifying "energy bugs" [14,15]. The existing papers describing the impact of design choices on the consumption of energy [16][17][18] evidence the need to further investigating this matter. In our research, we focus on studying the influence on it of the choice of programming languages.…”
Section: Introductionmentioning
confidence: 99%